Harmonization of Customary Criminal Acts in Bengkulu within the National Legal System - Mardhatillah, Mardhatillah; Ferdiansyah , Aldi; Satrya Putra, Raden; Al Fariq, Damar; Labuda Aziz, Fika (jurnal.unprimdn.ac.id, 2026)
The existence of customary law in Indonesia, including in Bengkulu Province, is part of the legal pluralism that is still alive and thriving in society. However, in practice, the implementation of customary criminal acts often faces challenges in its integration with the national legal system, particularly regarding the dualism of case resolution, legal certainty, and protection of human rights. This condition raises the need for harmonization between customary criminal law and national law to create a just and effective legal system. This study aims to analyze the forms and characteristics of customary criminal acts in Bengkulu and formulate an appropriate harmonization model within the framework of the national legal system. The research method used is normative legal research with a statutory and conceptual approach, through a qualitative descriptive analysis of primary, secondary, and tertiary legal materials. The results show that customary criminal acts in Bengkulu have a communal and restorative character oriented towards restoring social relations. Harmonization can be achieved by strengthening the recognition of customary law in regulations, integrating the principles of restorative justice into the criminal justice system, and establishing limits on the types of cases that can be resolved through customary law. Thus, this harmonization is able to maintain a balance between the local values ​​of indigenous communities and the principles of national law.